Anomalous Propagation in Low Index Contrast Metamaterials: Assessment of the Beam Collimation Condition - Jun Tan; Weiwei Song; Wei Jiang (International Journal of Optics)
Anomalous beam propagation in low index-contrast metamaterials has been analyzed. The condition for a well-collimated beam is found to be depending on the beam width and the pertinent Fourier component of the dielectric function. Guided by this condition, an ultra-compact metamaterial structure is designed to deflect a light beam at a wide angle. The structure is tolerant to structural parameter deviation and has a wide bandwidth.